2017
DOI: 10.1093/glycob/cwx107
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-10: a new structural type of prototype galectin dimer and effects on saccharide ligand binding

Abstract: Galectin-10 (Gal-10) which forms Charcot-Leyden crystals in vivo, is crucial to regulating lymph cell function. Here, we solved the crystal structures of Gal-10 and eight variants at resolutions of 1.55-2.00 Å. Structural analysis and size exclusion chromatography demonstrated that Gal-10 dimerizes with a novel global shape that is different from that of other prototype galectins (e.g., Gal-1, -2 and -7). In the Gal-10 dimer, Glu33 from one subunit modifies the carbohydrate-binding site of another, essentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 43 publications
3
45
0
Order By: Relevance
“…65,66 In addition, recent findings indicate that Gal-10 dimerizes with a novel global shape that is different from that of other prototype galectins (eg, Gal-1, Gal-2, and Gal-7) and may essentially inhibit disaccharide binding. 65,67 The lack of binding to ß-galactosides FIG 6. CLC/Gal-10-deficient (knockdown) eosinophils have fewer secondary granules, a nonproliferative phenotype, decreased MBP-1 expression, and increased secretion of EDN in response to PAF stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…65,66 In addition, recent findings indicate that Gal-10 dimerizes with a novel global shape that is different from that of other prototype galectins (eg, Gal-1, Gal-2, and Gal-7) and may essentially inhibit disaccharide binding. 65,67 The lack of binding to ß-galactosides FIG 6. CLC/Gal-10-deficient (knockdown) eosinophils have fewer secondary granules, a nonproliferative phenotype, decreased MBP-1 expression, and increased secretion of EDN in response to PAF stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…In the asymmetric unit of the Gal-10 crystal, there is only one Gal-10 monomer, a pseudomorph that did not accurately display the global form of Gal10. Actually, Gal-10 is a homodimeric protein in solution [ 25 ].…”
Section: Ambiguous History Of Clc Protein/galecin-10mentioning
confidence: 99%
“…A solid phase assay showed that Gal-10 could bind weakly to lactose and n -acetyl- d -glucosamine conjugated to agarose [ 23 , 26 ]. However, three contradictory results showed that the weak carbohydrate binding activity may be attributed to wild type Gal-10 binding to the cross-linked agarose (or Sepharose) matrix and not to lactose [ 19 , 25 , 27 ], and the crystal structure of Gal-10 showed that it could bind mannose [ 23 ]. Recently, we generated a variant of Gal-10 (W127A) that exists as a monomer and can weakly bind to lactose-modified Sepharose [ 28 ].…”
Section: Ambiguous History Of Clc Protein/galecin-10mentioning
confidence: 99%
See 2 more Smart Citations